Morphine induces physiological, structural, and molecular benefits in the diabetic myocardium. Issue 3 (14th February 2021) - Zemljic‐Harpf, Alice E.; See Hoe, Louise E.; Schilling, Jan M.; Zuniga‐Hertz, Juan P.; Nguyen, Alexander; Vaishnav, Yash J.; Belza, Gianna J.; Budiono, Boris P.; Patel, Piyush M.; Head, Brian P.; Dillmann, Wolfgang H.; Mahata, Sushil K.; et al.
Abstract: The obesity epidemic has increased type II diabetes mellitus (T2DM) across developed countries. Cardiac T2DM risks include ischemic heart disease, heart failure with preserved ejection fraction, intolerance to ischemia‐reperfusion (I‐R) injury, and refractoriness to cardioprotection. While opioids are cardioprotective, T2DM causes opioid receptor signaling dysfunction. We tested the hypothesis that sustained opioid receptor stimulus may overcome diabetes mellitus‐induced cardiac dysfunction via membrane/mitochondrial‐dependent protection. In a murine T2DM model, we investigated effects of morphine on cardiac function, I‐R tolerance, ultrastructure, subcellular cholesterol expression, mitochondrial protein abundance, and mitochondrial function. T2DM induced 25% weight gain, hyperglycemia, glucose intolerance, cardiac hypertrophy, moderate cardiac depression, exaggerated postischemic myocardial dysfunction, abnormalities in mitochondrial respiration, ultrastructure and Ca 2+ ‐induced swelling, and cell death were all evident. Morphine administration for 5 days: (1) improved glucose homeostasis; (2) reversed cardiac depression; (3) enhanced I‐R tolerance; (4) restored mitochondrial ultrastructure; (5) improved mitochondrial function; (6) upregulated Stat3 protein; and (7) preserved membrane cholesterol homeostasis. These data show that morphine treatment restores contractile function, ischemic tolerance, mitochondrial structure and function, and membrane dynamics in type II diabetic hearts. These findings suggest potential translational value for short‐term, but high‐dose morphine administration in diabetic patients undergoing or recovering from acute ischemic cardiovascular events.